REFLECTION OF TRANSPORT LOGISTICS’ GRADUATES COMPETENCES IN THE VACANCY NOTICES FOR TRANSPORT MANAGERS POSITIONS - Ginavičienė, Jurgita; Piščikienė, Inga; Sprogytė-Bredelienė, Indrė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The contemporary landscape of the logistics industry is evolving, introducing fresh challenges for companies. Consequently, it is imperative to focus on the competency of employees and anticipate the skills that will be essential in the future. Therefore, it is important to not only identify professional competences of the logistics graduates but also to make sure that they coincide with the skills required by the labour market. To achieve this end, vacancy notices published in an online media (CV bank) in the last quarter of 2023 were collected and analysed. Then, the obtained results were compared to the identified competences of the graduates of Transport Logistics in 2023 at Vilnius College of Technologies and Design. The article reveals that vast majority of the graduates of Transport Logistics at the Vilnius College of Technology and Design have knowledge and skills that by large reflect the requirements laid out in the analysed vacancy notices.